ANALISA KAPASITAS TINGKAT PELAYANAN LALU LINTAS TANPA SINYAL PADA PERSIMPANGAN JALAN GALUNGGUNG â JALAN TERUSAN SURABAYA, MALANG JAWA TIMUR - De Jesus, Agusto; Rahma, Pamela Dinar (eUREKA : Jurnal Penelitian Mahasiswa Teknik Sipil dan Teknik Kimia, 2017)
Malang is the second major city after the city of Surabaya in East Java with tourist potential and its economy is growing. The activities such as malls, markets, parks, campuses, tourist areas, office activities and other activities are factors that make this street has a solid activity that led to the problem - the problem of transportation one bottleneck that resulted in road capacity has declined, survey or research used methods of data retrieval with Manual method Counter at Jalan Galunggung Canal road Surabaya Lowokwaru District Malang for the purpose of calculating the value of the traffic volume, speed, capacity and level of service is to conduct a survey for 14 days (2 weeks) (starting at 6:00 pm - 22:00 pm) and the data obtained from the survey of traffic volume, vehicle speed and road geometric data were then analyzed using the Indonesian Highway Capacity Manual (MKJI) 1997. Based on the analysis, peak hour volume on Jalan Surabaya Galunggung Canal road 2832 smp / hours, a capacity of 3140, 7 and level of service (LOS) is E. Keywords: capacity, degree of saturation and analysis service levels